2010
DOI: 10.1093/ndt/gfq505
|View full text |Cite
|
Sign up to set email alerts
|

The finding of reduced estimated glomerular filtration rate is associated with increased mortality in a large UK population

Abstract: This study demonstrates a graded association between reduced renal function as represented by eGFR and mortality in a UK population. The all-cause and cardiovascular mortality risk increases sharply when estimated GFR falls < 45 mL/min/1.73 m(2). The association between an eGFR measured between 45 and 65 mL/min/1.73 m(2) and cardiovascular mortality persists in this cohort and highlights the ongoing uncertainty in accurately categorizing renal dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Previous work has demonstrated that patients with reduced renal function have worsening outcomes as their condition progresses 15. This study highlights that as patients enter the phase of their illness when dialysis is needed, they require additional support, often in a hospital setting.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Previous work has demonstrated that patients with reduced renal function have worsening outcomes as their condition progresses 15. This study highlights that as patients enter the phase of their illness when dialysis is needed, they require additional support, often in a hospital setting.…”
Section: Discussionmentioning
confidence: 78%
“…We have a high prevalence of CKD in Northern Ireland and we have previously demonstrated this condition's significant association with increased morbidity and mortality 15. It therefore seemed likely that patients with renal disease requiring dialysis (ESRD) would represent an even greater clinical challenge leading to additional resource utilisation.…”
Section: Introductionmentioning
confidence: 99%
“…age, diabetes, ethnicity, deprivation, and other comorbidity (3,4), and in immunocompromised patients, the chance of infection may further increase these risks.…”
mentioning
confidence: 99%
“…Advanced CKD (stage 4-5), is associated with an increased relative risk (RR) of death of around 2.5-fold and a RR of kidney failure, as defined by a requirement for renal replacement therapy (RRT) of up to 50-fold compared to that of age-matched individuals with ‘normal' kidney function [28,29,30,31,32]. Matsushita et al confirmed that both CKD and albumin:creatinine ratio (ACR) predict all cause and CVD mortality in the general population [33].…”
Section: Why Use Acei/arbs In Earlier Stages Of Ckd?mentioning
confidence: 99%